Cross-Border Consumer Disputes in the Digital Marketplace: Rethinking Jurisdiction and Law in Global E-Commerce Governance - Taufiqurokhman; Sara, Rineke; Suseno, Wahyu Hanggoro; Zakaria, Ricky Muhamad (Indonesian Scientific Publication, 2025)
Cross-border e-commerce has created unprecedented opportunities for global trade but also introduced complex legal challenges regarding jurisdiction and applicable law in consumer disputes. This article explores how legal systems particularly those of the European Union (EU), the United States (US), ASEAN, and Indonesia govern jurisdiction and applicable law in business-to-consumer (B2C) e-commerce transactions. Using a doctrinal and comparative legal method, the study analyzes key instruments such as the Brussels I Recast, Rome I and II Regulations, Hague Conventions of 2005 and 2019, and relevant national laws. Case law from the CJEU and US courts is used to illustrate doctrinal interpretations, with attention to the targeting test, forum-selection enforceability, and protection of consumer rights. Procedural tools such as the Hague Service and Evidence Conventions are also examined. Findings reveal that while the EU offers a harmonized, consumer-focused regime, enforcement across borders remains inconsistent. The Hague 2019 Convention presents a pathway toward enforceability but requires broader ratification. The US system emphasizes contractual freedom, often limiting consumer protections. Regional efforts, particularly in ASEAN and Indonesia, demonstrate varied progress in legal harmonization. Jurisdictional ambiguity, enforcement gaps, and fragmented legal standards continue to affect legal certainty in cross-border e-commerce. The article concludes that harmonized jurisdictional and applicable law standards, coupled with technological and institutional innovation, are necessary to ensure consumer protection and support legal predictability in global digital markets.